Relationship between Information Skills and Antiretroviral Adherence in People Living With HIV/AIDS - Lailiah, Novianti; Nursalam, Nursalam; Kurniawati, Ninuk Dian (Universitas Airlangga, 2021)
Introduction: Adherence in ARV therapy is an important mechanism in preventing drug resistance. The level of adherence is influenced by several factors, one of which is the information skills factor. This study aims to analyze the relationship between information skills and ARV adherence in People Living With HIV/AIDS (PLWHA).Method: This was a cross-sectional approach with a sample size of 100 respondents who were selected through simple random sampling technique. The inclusion criteria for respondents were PLWHA who were undergoing ARV therapy, cooperative, aged 20-60 years. The instrument used was information skills questionnaire and Medical Adherence Rating Scale (MARS). The data were analyzed using descriptive analysis and logistic regression test with p value â‰¤ 0.05.Results: Information skills were associated with ARV adherence (p = 0.01). Information skills consisting of knowledge about HIV/AIDS and ARV therapy can increase ARV adherence in PLWHA with indicators taking drugs regularly and have medical control on schedule.Conclusions: The information skills factor has an effect on ARV adherence. Increasing information skills can be done through educational activities or peer-group support aimed at gaining insight into disease and treatment, especially for newly diagnosed PLWHA.